Addressing the "Bias Gap": A Research-Driven Argument for Critical Support of Plurilingual Scientists' Research Writing. (October 2019) - Corcoran, James
This article outlines findings from a case study investigating attitudes toward English as the dominant language of scientific research writing. Survey and interview data were collected from 55 Latin American health and life scientists and 7 North American scientific journal editors connected to an intensive scholarly writing for publication course. Study findings point to competing perceptions (scientists vs. editors) of fairness in the adjudication of Latin American scientists' research at international scientific journals. Adopting a critical, plurilingual lens, I argue that these findings demand a space for more equity-driven pedagogies, policies, and reflective practices aimed at supporting the robust participation of plurilingual scientists who use English as an additional language (EAL). In particular, if equity is indeed a shared goal, there is a clear need for commitment to ongoing critical self-reflection on the part of scientific journal gatekeepers and research writing support specialists.